Modeling the Effect of Surface Energy on Stressed Grain Growth in Cubic Polycrystalline Bodies - M., Jamshidian; P., Thamburaja; T., Rabczuk (Elsevier Ltd, 2016)
A recently-developed constitutive theory of stressed grain growth is augmented to include the effect of excess surface energy via a surface effect state variable. The new constitutive theory is implemented into a coupled finite-element and phase-field computational framework. Through three-dimensional simulations, the new constitutive model is shown to be capable of predicting the experimental data of the annealing-induced texture transition in polycrystalline copper thin films of different thicknesses attached to a polyimide substrate. Our simulations show that the grain growth driving force arising from the through-film thickness grain boundary curvature plays a prominent role in such a transitional behavior.